2011
DOI: 10.1371/journal.pone.0024764
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Zebrafish In Vivo with Second-Harmonic Generation Reveals Shortened Sarcomeres Associated with Myopathy Induced by Statin

Abstract: We employed second-harmonic generation (SHG) imaging and the zebrafish model to investigate the myopathy caused by statin in vivo with emphasis on the altered microstructures of the muscle sarcomere, the fundamental contractile element of muscles. This approach derives an advantage of SHG imaging to observe the striated skeletal muscle of living zebrafish based on signals produced mainly from the thick myosin filament of sarcomeres without employing exogenous labels, and eliminates concern about the distortion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 48 publications
3
35
0
1
Order By: Relevance
“…In agreement with previously reported zebrafish optical characterization, spherical aberration is a main contributor to resolution and SNR degradation (Bourgenot et al, 2012;Gould et al, 2012;Rueckel et al, 2006). As Zebrafish generate less aberration than the oncological sample (Figure 71), the system corrections (Z5--Z14) contributed Zebrafish produce substantial second--harmonic (SHG) signal (Huang et al, 2011).…”
Section: Adaptive Optics In Vivosupporting
confidence: 90%
“…In agreement with previously reported zebrafish optical characterization, spherical aberration is a main contributor to resolution and SNR degradation (Bourgenot et al, 2012;Gould et al, 2012;Rueckel et al, 2006). As Zebrafish generate less aberration than the oncological sample (Figure 71), the system corrections (Z5--Z14) contributed Zebrafish produce substantial second--harmonic (SHG) signal (Huang et al, 2011).…”
Section: Adaptive Optics In Vivosupporting
confidence: 90%
“…26,28,29 The label-free nature of sarcomeric SHG has been utilized to study sarcomere microarchitecture in muscular dystrophy, 30,31 myofibrilogenesis, 32 and drug-induced myopathy. 33 It has also been developed as a technique to study local actin-myosin cross-bridging 28,29 and in vivo contractile dynamics in skeletal muscle. 34 Boulesteix et al have used it to measure sarcomere length with a reported accuracy of 20-nm in relaxed and tetanic frog cardiac myocytes.…”
Section: Methodsmentioning
confidence: 99%
“…The operating range of L s in cardiomyocytes within the left ventricular wall has been determined using hearts arrested and chemically fixed at experimentally controlled pressures, with spacing between electron dense Z lines measured using electron microscopy (30) or transmitted light microscopy (11). These approaches require careful tissue preparation to avoid fixation artifacts associated with shrinkage resulting in underestimation of L s [e.g., see Huang et al (16)]. Furthermore, fixed preparations limit L s evaluation to a single filling pressure in each heart, effectively preventing evaluation of the pressure versus L s relationship in a single heart.…”
Section: Discussionmentioning
confidence: 99%